2021
DOI: 10.3389/fpsyg.2021.700272
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ Selective Visual Attention Is Dependent on Maternal Affect and Emotional Context

Abstract: Development of selective attention during the first year of life is critical to cognitive and socio-emotional skills. It is also a period that the average child’s interactions with their mother dominate their social environment. This study examined how maternal negative affect and an emotion face prime (mother/stranger) jointly effect selective visual attention. Results from linear mixed-effects modeling showed that 9-month olds (N=70) were faster to find a visual search target after viewing a fearful face (re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 99 publications
1
7
0
Order By: Relevance
“…The visual search task was adapted for infants based on procedures from Juvrud et al. (2021) and Haas et al. (2016).…”
Section: Methodsmentioning
confidence: 99%
“…The visual search task was adapted for infants based on procedures from Juvrud et al. (2021) and Haas et al. (2016).…”
Section: Methodsmentioning
confidence: 99%
“…The participants wear noise-canceling headphones while completing a larger battery of experimental tasks. The tasks assessed IQ [27], visual attention [28,29], emotional processing [30], working memory [31], and risk-taking [32] with written instructions in Arabic. The task was identical for all ages and all participants had the same amount of time to complete the task.…”
Section: Procedures and Designmentioning
confidence: 99%
“…In turn, mutual gaze has been associated with visual attention in the first postnatal year of life 38 . The impact of maternal distress on mother-infant interactions 39 and maternal sensitivity 40 have been related to infants’ selective attention 41 and gaze-following ability 42 .…”
Section: Introductionmentioning
confidence: 99%
“…Though it seems evident that a mother’s mental health, during both antenatal 23 , 33 , 34 , 43 46 and postpartum 23 , 37 , 38 , 41 , 45 , 46 , has a significant impact on offspring’s attention, the underlying mechanisms are still unclear. Previous evidence has shown that the complex and dynamic interactions between multiple biological, psychological and environmental factors contribute to both mothers’ mental health and children’s attention.…”
Section: Introductionmentioning
confidence: 99%